Particle grouping in standing and moving wave velocity fields. (13th September 2010) - Katoshevski, David; Shakked, Tal; Sazhin, Sergei S.
The parameters which control particle grouping characteristics in a standing wave velocity field are elucidated. A mathematical model for particle grouping in a standing wave velocity field is compared with the one describing their grouping in a moving wave velocity field. Two grouping/non-grouping regimes are identified and described. It is pointed out that particle flow in a standing wave velocity field has a smaller range of operating conditions, where grouping is expected, compared with the particle flow in the moving wave.